2015
DOI: 10.1371/journal.pone.0125386
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Dispersal and Potential Environmental Transmission of the Amphibian Chytrid Fungus (Batrachochytrium dendrobatidis)

Abstract: Dispersal and exposure to amphibian chytrid fungus (Batrachochytrium dendrobatidis, Bd) is not confined to the aquatic habitat, but little is known about pathways that facilitate exposure to wild terrestrial amphibians that do not typically enter bodies of water. We explored the possible spread of Bd from an aquatic reservoir to terrestrial substrates by the emergence of recently metamorphosed infected amphibians and potential deposition of Bd-positive residue on riparian vegetation in Cusuco National Park, Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 53 publications
4
37
0
1
Order By: Relevance
“…This trend was consistent among host species, regardless of the habitat type that each species occupied. Even though we consider perches to contain an accurate representation of the microbiota found in the microhabitat that each frog species occupies, it is possible that some frog OTUs might be rubbed off onto perches in the same way Bd is (Kolby et al, 2015). However, even considering this caveat, we found clear differences between frog and perch samples.…”
Section: Discussionmentioning
confidence: 80%
“…This trend was consistent among host species, regardless of the habitat type that each species occupied. Even though we consider perches to contain an accurate representation of the microbiota found in the microhabitat that each frog species occupies, it is possible that some frog OTUs might be rubbed off onto perches in the same way Bd is (Kolby et al, 2015). However, even considering this caveat, we found clear differences between frog and perch samples.…”
Section: Discussionmentioning
confidence: 80%
“…Field surveillance (Kriger & Hero, ), broad‐scale modelling (Bielby, Cooper, Cunningham, Garner, & Purvis, ) and experimental work (Becker et al., ) have established a general negative association between infection risk and host life histories that are biased towards terrestrial habitats. However, laboratory experiments have found that Bd can proliferate in hosts (Raffel et al., ) and survive outside of hosts (Kirshtein, Anderson, Wood, Longcore, & Voytek, ; Kolby et al., ) in sufficiently wet terrestrial habitats. There is also evidence for cryptic but persistent infection of terrestrial hosts (Minting, ) and documented cases of Bd infecting fully terrestrial amphibians (Kolby et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, laboratory experiments have found that Bd can proliferate in hosts (Raffel et al., ) and survive outside of hosts (Kirshtein, Anderson, Wood, Longcore, & Voytek, ; Kolby et al., ) in sufficiently wet terrestrial habitats. There is also evidence for cryptic but persistent infection of terrestrial hosts (Minting, ) and documented cases of Bd infecting fully terrestrial amphibians (Kolby et al., ). Thus, whether increased terrestrial use can regulate either the probability of infection or post‐infection parasite proliferation over short time spans associated with routine habitat switching is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the transfer of Bd from the aquatic habitat to the terrestrial habitat could occur from recent metamorphs of species with aquatic larval stages and then infect terrestrial direct developing species, for example, species in the genus Craugastor (Bielby et al 2008;Kobly et al 2015a;Lötters et al 2009). The presence of chytrid spores in rain drops in recent studies in Cusco, Peru suggests that strong winds and rain could help in the spread of Bd spores (Kolby et al 2015b). High altitude and small geographic range are reported by Bielby et al (2008) as the factors driving the relation between Bd positive, rapidly declining species and other Bd positive species.…”
Section: Groupmentioning
confidence: 99%